International TV series distribution on Chinese digital platforms: marketing strategies and audience engagement - Gilardi, Filippo; Lam, Celia; Tan, K. Cohen; White, Andrew; Cheng, Shuxin; Zhao, Yifan (SAGE, 2018)
The relationship between online media platforms in China and fan groups is a dynamic one when it comes to the distribution of international TV series and other media content, as media platforms incorporate user-generated content to encourage or foster audience engagement. Through a series of case studies, this article investigates how international TV series are acquired, distributed, marketed and curated on Chinese online video platforms. This helps to identify specific strategies and themes used by these platforms to promote international content and engage users. These marketing techniques, however, are not always as successful as expected, suggesting the need for a closer examination of the types of engagement sought by media platforms, and the ways in which Chinese audiences have responded within their cultural context.